The Identification of a Novel Thiopurine S-Methyltransferase Allele, TPMT*45, in Korean Patient with Crohn’s Disease - Ha C; Kim ES; Kwon Y; Choe YH; Kim MJ; Lee SY (Pharmacogenomics and Personalized Medicine, 2020)
Changhee Ha,1 Eun Sil Kim,2 Yiyoung Kwon,2 Yon Ho Choe,2 Mi Jin Kim,2 Soo-Youn Lee1,3 1Department of Laboratory Medicine and Genetics, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Korea; 2Department of Pediatrics, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Korea; 3Department of Clinical Pharmacology and Therapeutics, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, KoreaCorrespondence: Mi Jin KimDepartment of Pediatrics, Samsung Medical Center, Sungkyunkwan University School of Medicine, 81 Irwon-ro, Gangnam-gu, Seoul 06351, KoreaTel +82 2 3410 0951Fax +82 2 3410 0043Email mijin1217.kim@samsung.comSoo-Youn LeeDepartment of Laboratory Medicine and Genetics, Department of Clinical Pharmacology and Therapeutics, Samsung Medical Center, Sungkyunkwan University School of Medicine, 81 Irwon-ro, Gangnam-gu, Seoul 06351, KoreaTel +82 2 3410 1834Fax +82 2 3410 2719Email suddenbz@skku.eduAbstract: Pediatric Crohn’s disease (CD) carries a higher genetic susceptibility and an increased risk of a more aggressive disease course than adult CD. Treatment of CD is based on immunomodulatory drugs, such as thiopurines. The enzyme mainly involved in drug metabolism is thiopurine S-methyltransferase (TPMT). An increased concentration of drug metabolites can cause adverse drug effects, such as myelosuppression and hepatotoxicity; therefore, assessing the activity of TPMT is essential both before and during treatment. TPMT genotyping result is not affected by previous thiopurine dose and currently is the primary component of TPMT activity and disease monitoring. Until now, more than 40 allelic variants of the TPMT gene have been reported, with most of them having an uncertain or no enzyme function. In this article, we report the first case of a novel TPMT allele, TPMT*45, that was identified in a Korean girl with CD whose findings suggested decreased TPMT activity. This newly observed variant is caused by a single nucleotide polymorphism resulting in nonsense mutation (c.676C>T, p.R226*) and the partial loss of amino acids in the TPMT protein. Initially, the patient began azathioprine at a standard dosage (1.5 mg/kg/day), and her laboratory results, including red blood cell (RBC) TPMT activity (6-methylmercaptopurine 2.68 nmol/mL/h and 6-methylmercaptopurine riboside 4.82 nmol/mL/h) along with thiopurine metabolite levels (6-thioguanine nucleotides 479.3 pmol/8× 108 RBC), suggested an enzyme deficiency. The thiopurine dose was reduced to half (0.7 mg/kg/day), and the follow-up metabolite results as well as the associated inflammatory markers were continuously within reference ranges. Along with an improvement in the patient’s subjective reports and clinical symptoms, the patient demonstrated a good treatment response to the adjusted dose. The results of our report illustrate the importance of TPMT genotyping and pharmacogenetic-based thiopurine dose adjustment. Further research should focus on the functional characterization and impact on this novel allele’s treatment effect.Keywords: TPMT*45, Crohn’s disease, thioupurine, single nucleotide polymorphism, TPMT activity, drug metabolism